PEMBERDAYAAN PENDIDIKAN BAHASA INGGRIS ANAK USIA DINI: IMPLEMENTASI METODE TPR DAN PICTURE SEQUENCE DI RUMAH PERADABAN BANTEN - Yuliyanti, Novy; Romadhon, Romadhon (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2024)
The English language mentoring program for children at Rumah Peradaban Banten, utilizing the Total Physical Response (TPR) and Picture Sequence methods, aimed to enhance the English skills of the participating children. The TPR method, which combines physical movement with language learning, proved effective in introducing new vocabulary in an enjoyable way. Meanwhile, the Picture Sequence method engaged children in creating stories based on a series of images, helping them develop critical thinking, enrich vocabulary, and practice both speaking and writing skills in English. This activity was conducted on Sunday, July 28, 2024, and August 4, 2024, from 8:00 AM to 10:00 AM, with 57 participants who demonstrated high enthusiasm throughout the mentoring sessions. The results of the pre-test and post-test showed improvement in the participants' English abilities, with an average score increase of 25-40 points. The success of this mentoring program proves that TPR and Picture Sequence are effective approaches for teaching English to children, yielding positive impacts on their skills. This program not only provided a fun learning experience but also successfully improved the children’s English abilities, making it a model that can be replicated in other communities to enhance the quality of English education.